The Surgical Care Practitioner role in Achilles tendon re-rupture: A case study. Issue 12 (December 2021) - Julies, Elda; Williams, Tim; Hall, Susan
The value of a Surgical Care Practitioner to an orthopaedic team is demonstrated in this case study of a patient who presented with a re-ruptured Achilles tendon. It highlights the role the practitioner plays in the patient journey and illustrates it's value throughout the clinical course from consultation through to discharge. The Surgical Care Practitioner, as a member of the extended surgical team can help to explain the diagnosis and associated treatment options, facilitate informed consent and provide expert procedural assistance to the surgeon. A Surgical Care Practitioner is ideally placed to answer patient queries and aid in rehabilitation.